2017
DOI: 10.1108/er-10-2016-0199
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between job embeddedness and employees’ life satisfaction

Abstract: Purpose The purpose of this paper is to explore relationships between organisation embeddedness and life satisfaction, and community embeddedness and life satisfaction. The study also examined relationships between each sub-dimension of organisation embeddedness and community embeddedness and life satisfaction. These sub-dimensions are “links”, “fit” and “sacrifice”. Design/methodology/approach Data were collected from 549 employees in organisations located in four major business centres in South Africa. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 92 publications
(150 reference statements)
4
53
2
3
Order By: Relevance
“…Furthermore, DeConinck and Johnson (2009) emphasised that employees with a low level of organisational commitment are more likely to show negative work outcomes such as job-search behaviour, turnover intention and actual turnover. Turnover intention can be referred to of employees' awareness regarding the possibility of leaving organisation in the near future (Mowday et al, 1982;Ampofo et al, 2017;Li et al, 2017), and it represents the strongest predictor of actual turnover behaviour (Joo and Park, 2010). The present research confirms that employees' turnover intentions negatively related to organisational commitment (Joo and Park, 2010;Lee and Bruvold, 2003;Fazio et al, 2017;Lim et al, 2017).…”
Section: Job Embeddedness Organisational Commitment and Intention Tosupporting
confidence: 74%
“…Furthermore, DeConinck and Johnson (2009) emphasised that employees with a low level of organisational commitment are more likely to show negative work outcomes such as job-search behaviour, turnover intention and actual turnover. Turnover intention can be referred to of employees' awareness regarding the possibility of leaving organisation in the near future (Mowday et al, 1982;Ampofo et al, 2017;Li et al, 2017), and it represents the strongest predictor of actual turnover behaviour (Joo and Park, 2010). The present research confirms that employees' turnover intentions negatively related to organisational commitment (Joo and Park, 2010;Lee and Bruvold, 2003;Fazio et al, 2017;Lim et al, 2017).…”
Section: Job Embeddedness Organisational Commitment and Intention Tosupporting
confidence: 74%
“…A positivist paradigm of research design is adopted for this study because its epistemological positioning allows researchers a legitimate way of primary data generation, by interacting with people, asking questions and recording responses through standard questionnaires (Ampofo et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Over the years, several researchers have worked on the relations between embeddedness, performance and turnover. Their empirical findings suggested that JE characteristics predict both the employee's intention to quit and actual turnover (Choi and Kim, 2015;Ampofo et al, 2017). Bergiel et al (2009) established the significance of JE as a link amongst organizational practices and purpose to leave.…”
Section: Job Embeddedness (Je) and Voluntary Turnover Intention (Vtoi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al (2012) found a strong correlation between JE dimensions, job satisfaction, and organizational commitment. Ampofo et al (2017) found the effect of a colleague's JE on individual employee turnover, and the results showed that at the individual level, organizational commitment is a stronger predictor of voluntary separation compared with JE. Emotional commitment is relevant 2017Roles of engagement JE Manufacturing industries Engagement, job performance and intention to leave Ng & Feldman (2014) Organizational embeddedness and insomnia issues Managers array of industries Performance, labor member exchange & organization-based self-esteem Bergiel et al (2009) Human resource practices, JE and quite State department Human resource practices and intention to quit N. Ferreira & Coetzee (2013) Embeddedness on bank employees and commitment Services industry Turnover contagion and job search behavior Wijayanto & Kismono (2004) Organizational citizenship behavior Hospitality firm Social capital and human capital Allen et al (2016) JE means "Stuck" environments Business industries Organizational citizenship behavior Wilson (2010) JE survey items for education Education sector Adventure education population N. Ferreira & Coetzee (2013) Embeddedness on bank employees and commitment Services industry Work-family conflict and intention to leave Karatepe (2011) Coworker and perceived organizational support Hotel employees Job outcomes and organizational justice Acquah (2015) HRM practices and turnover intention Hotel industry Voluntary turnover Morganson et al (2015) Embeddedness theory and promote persistence Students universities Employee retention TOI Wheeler et al 2012How do employee effect Education sector Conscientiousness and performance Holtom et al (2012) Mediation effect organizational citizenship behavior between JE and TOI…”
Section: Findings Discussion and Future Directionsmentioning
confidence: 99%